O Aconselhamento Pastoral Virtual: a partir de um estudo da Telefonseelsorge na Internet e da Maranataonline - Krause, Renilda (2010)
The object of this thesis is to present the virtual world as a new pleace for the Pastoral Counseling and a way of updating the links among the Church and the society, also to reveal the Gospel in the virtual language and relationships. Initially, it is discussed subjects related to Internet communication and the interpretation according to the time in which global and local culture and society take place. There will also be presented ideas that came up with the development of the comunication through out computers, such as the virtual one and its modality, the virtual communities and the body virtualization. On the second chapter, it is presented an analisis of the theoretical, methodological and technical basis of the Pastoral Counseling done through the Internet, surching to trace its potentials as well as the limits of this helping tool. The third part is consisted of a study of two cases, the Telefonseelsorge in the Internet (Germany) and Maranataonline (Brazil), where the method of Netnography and interviewing are used in order to discuss chances and limits of Pastoral Counseling done on the Internet mainly through site resources and eletronic mails. On the last part, conclusions are taken confirming that the Internet is a new way of communication that provides a lot of potentials such as an instantaneous intergration, the boundaries dilution, the anonymity,the movable immobility, which represents the chances of the Pastoral Counseling to meet all sorts of people, in different situations, there where they are, and this, at Internet age means a global and virtual space.